Differential responses of selectively bred mussels (Perna canaliculus) to heat stress—survival, immunology, gene expression and microbiome diversity - Ericson, Jessica A.; Laroche, Olivier; Biessy, Laura; Delorme, Natalí J.; Pochon, Xavier; Thomson-Laing, Jacob; Ragg, Norman L. C.; Smith, Kirsty F. (Frontiers in Physiology, 2024)
New Zealand’s green-lipped mussel (Perna canaliculus) is an ecologically and economically important species. Marine heatwaves are increasing in frequency around NZ’s coastline, and these events are correlated with increased stress and mortality of some aquaculture species. This study aimed to identify general biomarkers of heat stress in P. canaliculus and to assess whether responses differed between genetically distinct selectively bred mussels. We exposed three families of selectively bred mussels (families A, B and C) to three seawater temperature regimes in the laboratory: (1) a ‘control’ treatment (ambient 12 °C), (2) a 26 °C heat challenge with a subsequent recovery period, and (3) a sustained 26 °C heat challenge with no recovery. We investigated whether the survival, immune response (hemocyte count and viability, oxidative stress and total antioxidant capacity), hemocyte gene expression and gill microbiome differed between the families during the temperature challenges. In the sustained heat-stress treatment, family A had the highest survival rate (42% compared with 25% and 5% for families C and B, respectively). Gene expression levels significantly shifted during thermal stress and differed between families, with family A more dissimilar than families B and C. Family C had substantially more genes impacted by temperature treatment and timepoint than the other families, while family B had very little genes/pathways that responded to thermal stress. Genes related to heat shock proteins (HSPs) and immune responses (e.g. AIF1, CTSC, TOLL8, CASP9, FNTA, AHCY, CRYAB, PPIF) were upregulated in all families during heat stress. Microbiome species-richness differed between families before and during heat-stress, with family A having a distinctly different microbiome flora than the other families. Microbial diversity changed similarly in all families exposed to prolonged heat-stress, with species of Vibrio and Campylobacter increasing in these mussels. Our study highlights the use of non-lethal sampling of hemocytes as a diagnostic tool to explore the immune response and gene expression of selectively bred mussels, to predict their response to ocean warming. This approach can identify potential thermotolerant candidates for further selective breeding, which may increase the resilience of the mussel aquaculture industry in a warming ocean.